Spatial variability characteristics of soil physicochemical properties in fixed-axis and tracking tilted single-axis photovoltaic panels in qinghai desert areas - Yue, Shengjuan; Guo, Mengjing; Yuan, Bo; Ye, Deli; Ma, Hongyuan; Bai, Wenwen (Frontiers in Environmental Science, 2025)
To clarify the influence of photovoltaic (PV) panels on the spatial distribution characteristics of soil properties in desert areas, the soil of fixed-axis (FIX) PV panels and tracking tilted single-axis (TTS) PV panels in the Gonghe large-scale PV power plant in the Qinghai desert was taken as the research object. The PV panels were divided into the south edge, the north edge, under and between panels. The soil in the undisturbed area outside the PV power plant was taken as the control area. The results showed that, except between the PV panels, the soil bulk density (BD) increased significantly at other locations of the TTS PV panels (p < 0.001), soil organic carbon (SOC), total carbon (TC) and total nitrogen (TN), and available nitrogen (AN) decreased significantly (−35.07%, −29.62%, −38.25%, and −32.86% under the panels, respectively), and the total phosphorus (TP) content was significantly decreased only in the north edge and between the panels (p < 0.01). Soil water content (SWC) of FIX PV panels increased significantly (+74.74% under the panels, p < 0.001), and pH decreased. Comparing the two types of PV panels, except the north edge, SWC, SOC, TN, SOC: TP, TN: TP, and AN were significantly higher in the FIX PV panels than in the TTS PV panels, and BD, total potassium (TK), and SOC: TN were considerably lower than in the TTS PV panels. There was no significant difference (p > 0.05) in soil quality and multifunctionality index in the PV panel area. The research results can provide theoretical support for soil restoration of PV power plants in desert grassland.